Theater in Prison: Extension and Research as formative paths in Theater Pedagogy (Urdimento: Revista de Estudos em Artes Cênicas, 2020)
This report refers to a student experience with an extension action and a research project on Theater and Penitentiary Education promoted by the Theater Degree Course at the Federal University of Amapá - UNIFAP. We tried to discuss the participation with the thematic project and how the extension practice became a scientific investigation on the relationship of doing theater with the prison space and the reflection of these actions in the student / teacher training of the undergraduates of the course in question.
Keywords: Theater; Prison; Extension; Search